2021
DOI: 10.3390/insects12030223
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of Two Cry-Binding Aminopeptidase N Isoforms Does Not Change Susceptibility of Aedes aegypti Larvae to Bacillus thuringiensis subsp. israelensis Cry4Ba and Cry11Aa Toxins

Abstract: The insecticidal Cry4Ba and Cry11Aa crystal proteins from Bacillus thuringiensis subsp. israelensis (Bti) are highly toxic to Ae. aegypti larvae. The glycosylphosphatidylinositol (GPI)-anchored APN was identified as an important membrane-bound receptor for multiple Cry toxins in numerous Lepidoptera, Coleoptera, and Diptera insects. However, there is no direct molecular evidence to link APN of Ae. aegypti to Bti toxicity in vivo. In this study, two Cry4Ba/Cry11Aa-binding Ae. aegypti GPI-APN isoforms (AeAPN1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Taking account of high Cry1Ac resistance caused by mutations in ABCC2 (1400-fold) and cadherin (549-fold) in H. armigera [ 49 , 63 ], it should be concluded that the contribution of HaAPN1 to Cry1Ac toxicity is negligible. Likewise, the knockout of APN1 in S. exigua and APN1 and APN2 in Aedes aegypti did not affect Cry1Ac, Cry1Ca, and Cry1Fa susceptibilities or Cry4Ba and Cry11Aa susceptibilities, respectively [ 64 , 65 ]. Drosophila melanogaster larvae expressing Manduca sexta APN1 (MsAPN1) were susceptible to Cry1Ac [ 66 ], having been considered as compelling evidence that APN1 is a Cry1A receptor.…”
Section: Receptor Interactionsmentioning
confidence: 99%
“…Taking account of high Cry1Ac resistance caused by mutations in ABCC2 (1400-fold) and cadherin (549-fold) in H. armigera [ 49 , 63 ], it should be concluded that the contribution of HaAPN1 to Cry1Ac toxicity is negligible. Likewise, the knockout of APN1 in S. exigua and APN1 and APN2 in Aedes aegypti did not affect Cry1Ac, Cry1Ca, and Cry1Fa susceptibilities or Cry4Ba and Cry11Aa susceptibilities, respectively [ 64 , 65 ]. Drosophila melanogaster larvae expressing Manduca sexta APN1 (MsAPN1) were susceptible to Cry1Ac [ 66 ], having been considered as compelling evidence that APN1 is a Cry1A receptor.…”
Section: Receptor Interactionsmentioning
confidence: 99%
“…Also, in A. aegypti two APNs have also been identified as receptors for Cry11Aa toxin [42]. However, individual or simultaneous CRISPR-Cas9 KO of these two APN in A. aegypti does not affected the susceptibility to Cry11Aa and Cry4Ba toxins suggesting that additional APN isoforms could compensate the lack of expression of the edited apn genes [43].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Guo et al [9][10][11] found that the MAPK signaling pathway regulates the Bt resistance of P. xylostella by regulating the differential expression of ALP, APN, and ABCC genes, while MAPK [10,12] is regulated by the juvenile hormone (JH) [13] and 20-hydroxyecdysone (20E). At present, Bt toxin receptors have been reported mainly including aminopeptidase (APN) [14][15][16][17][18], cadherin/cadherinlike (CAD) [19][20][21][22][23][24][25], alkaline phosphatase (ALP) [26,27] and ATP binding cassette (ABC) transporter [28][29][30][31][32][33][34][35][36][37]. With the development of further research, an increasing number of receptor proteins, genes, and resistance pathways [38][39][40] have been reported to be involved in the toxicity of Bt to insects and the resistance of insects to Bt toxins, including polycalin in this study.…”
Section: Introductionmentioning
confidence: 99%